2021
DOI: 10.1371/journal.ppat.1009534
|View full text |Cite
|
Sign up to set email alerts
|

Dual transcriptional analysis reveals adaptation of host and pathogen to intracellular survival of Pseudomonas aeruginosa associated with urinary tract infection

Abstract: Long-term survival of bacterial pathogens during persistent bacterial infections can be associated with antibiotic treatment failure and poses a serious public health problem. Infections caused by the Gram-negative pathogen Pseudomonas aeruginosa, which can cause both acute and chronic infections, are particularly challenging due to its high intrinsic resistance to antibiotics. The ineffectiveness of antibiotics is exacerbated when bacteria reside intracellularly within host cells where they can adopt a drug t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 73 publications
(139 reference statements)
3
54
1
Order By: Relevance
“…aeruginosa strains possess a widely conserved ability to invade 5637 cells and confirm the recent findings of Penaranda et al . [9]. Based on similar research in UPEC, it is likely that P.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aeruginosa strains possess a widely conserved ability to invade 5637 cells and confirm the recent findings of Penaranda et al . [9]. Based on similar research in UPEC, it is likely that P.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature has shown that P. aeruginosa can invade corneal cells, lung epithelial cells, and recently urinary epithelial cells [7–9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this information about ExoS and ExoT, many publications by us and others over several decades have demonstrated that P. aeruginosa strains encoding both exotoxins (invasive strains) can invade and thrive inside a variety of host cell types [34][35][36][37]. This includes multiple infection sites in vivo, such as the cornea, lung and bladder [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this information about ExoS and ExoT, many publications by us and others over several decades have demonstrated that P. aeruginosa strains encoding both exotoxins (invasive strains) can invade and thrive inside a variety of host cell types [34][35][36][37]. This includes multiple infection sites in vivo, such as the cornea, lung and bladder [36][37][38]. Yet, the intracellular lifestyle of P. aeruginosa is much less well understood than that of other facultative intracellular pathogens due to the persistent dogma that P. aeruginosa is an extracellular pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary tract infections (UTIs) are one of the most common types of infectious diseases, leading to substantial medical costs each year and showing a high rate of recurrence. 1 Pseudomonas aeruginosa is an important pathogen, responsible for about 7–11% of urinary tract infections. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%